Hydraulic transient analysis in pumping stations due to power failure. (Al-Mazak Closed Irrigation System), Kut, Iraq - Mohammed Najm Abdullah (Journal of Madenat Alelem University College, 2017)
This paper deals with the problems which may occur during transient state in pumping station in which pressure changes temporarily so much due to power failure that the network in pumping stations are damaged. A computer program was developed based on method of characteristics discussed by Chaudhry [1]. Some improvements were done in the technique used to meet the requirement of any problems may be take place in pumping stations. The developed program was applied to pumping stations in "Al-Mazak closed irrigation system" to treat the water hammering caused by power failure or sudden shutdown of the end valve. The results are presented for different assumptions and the suggested solutions to avoid any problem may be happened.